Pembentukan Karakter Rendah Hati Peserta Didik Dalam Al-Qur’an Surah Al-Furqan 63-64 Kajian Ilmu Pendidikan Islam - Fauziah, Hapsah; Mahpudz, Sahal (STAI Al-Musaddadiyah Garut, 2022)
Education and character development are crucial aspects of an individual’s life, as character significantly influences one's success. Therefore, it is essential to cultivate strong and positive character traits continuously. One such important trait is humility, known in Islam as